Upaya Pemulihan Citra Perum Perhutani: Studi Manajemen Public Relations - Tresna Wiwitan (MediaTor (Jurnal Komunikasi), 2005)
Regarding the significant decrease of Indonesia woodland, the management of wood resources becomes the main issue these days. The lack of professionalism attending this matter give bad publicity to Perum Perhutani who responsible to maintain wood resources. It is believed that Public Relations (PR) practices played a key role to improve the negative image of Perum Perhutani. Using PR planning steps such as defining PR problems, collecting data toward public opinions, finding key informants, and implementing community relation activities, the problems were solved successfully.